Kihívások és modellértékű válaszok : a dél-dunántúli városok átalakulása a 19. században - Kaposi, Zoltán (Közép-Európai Közlemények, 2012)
In my study I am analyzing the economical development of the two major cities (Pécs, Nagykanizsa) of the South Transdanubia in the 19th century. This region was suffering from low level of urbanization. The development of the two cities shows two completely different ways. The economical transformation of Pécs was similar to the industrialization in England: the manufacturing industry dominated. World famous family enterprises were founded in this time (the coal mine of Erste Donau Dampfschiffahrts gesellschaft, Zsolnay Porcelain Manufactory, Hamerli Glove Manufactory, Höfler Leather Manufactory, Angster Organ Manufactory). In the case of Nagykanizsa the trade was the most crucial factor in the urban development. The city was really lucky, due to the fact that it was located in the crossing of five roads and four railroads. In the 19th century the grain trade was dominant, while to the turn of the twentieth century the animal trade became the most important.